Abnormal emotional behavior in children and its relationship to televised violence - Wassan Nasser, Mohammed (Opción, 2019)
Many psychological and educational studies confirmed that children are influenced by what is directed to them from the media, especially television, which affects two senses of their senses at the same time; moreover the speed of their influence is due to the fact that they are still at impression stage. This paper aims to identify the relationship between the number of watching hours of televised violence and the abnormal emotional behavior in children, and the abnormal emotional behavior is diagnosed by (aggression, fear, anxiety, negative behavior, dependent behavior). The sample of research reached 240 child, their age range between 6-12 years, and the number of watching hours is (4) hours and more. The results of the study indicate that most of the sample has abnormal emo- tional disorders, and in the light of the results, a set of recommendations and suggestions were developed.